Association of tooth brushing behavior with risks of major chronic health outcomes: a scoping review - Hee-Jung Park; Nam-Hee Kim; Sun-Jung Shin; Hwa-Young Lee; Jin-Young Jeong (BMC Oral Health)
Abstract Background Oral hygiene behavior has been increasingly recognized as a potential contributor to chronic disease prevention. This scoping review aimed to synthesize existing evidence on the associations between tooth brushing behavior (as a proxy for oral hygiene) and major chronic health outcomes, including cardiovascular events (e.g., myocardial infarction, atrial fibrillation, heart failure), stroke (ischemic, hemorrhagic, and subarachnoid), hypertension (HTN), metabolic syndrome (MetS), and chronic kidney disease (CKD). Methods A comprehensive literature search was conducted using four databases: Ovid-MEDLINE, EMBASE, CINAHL, and the Cochrane Library. The study selection process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Two reviewers independently screened and selected eligible studies and extracted relevant data. A total of 142 full-text articles were assessed for eligibility. Results Twenty-one studies were included in the final review. Most studies reported that a lower frequency of tooth brushing was associated with a higher risk of cardiovascular events, stroke, HTN, MetS, and CKD. Additionally, several studies suggested that maintaining good oral hygiene in individuals with HTN or diabetes mellitus (DM) may be associated with a reduced risk of cardiovascular complications. Conclusion Frequent tooth brushing, as a key component of oral hygiene, may be associated with a reduced risk of several chronic health outcomes, particularly cardiovascular and metabolic diseases. However, the current body of evidence is predominantly based on observational studies. Further longitudinal and interventional research is warranted to clarify the directionality and potential causal pathways linking oral hygiene behavior to systemic health outcomes.